Cinéma, théâtre et psychanalyse : la question de l’acte et sa représentation - POIRSON-DECHONNE, Marion (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
Cinema, Theatre and Psychoanalysis: the Problem of Parapraxis and its Representation. At the intersection of the performing arts and psychoanalysis emerges the notion of act. This polysemic term has various meanings: missed act, agieren, psychoanalytic act, acting out, act of creation. If Freud and Lacan have theorized the notion of act, cinema and theater strive to represent its many facets. Today, Freud’s method of analyzing dream images has paved the way for figural analysis for the 7th art, focusing on exploring the incomplete dimension of some of his images. From La marquise d’O to the Mystères de Lisbonne, the altered quotation from the same painting, The nightmare of Füssli, which reveals the emergence of desire, comes to symbolize the representation of the Other Scene by cinema. Généalogies d’un crime, by Raoul Ruiz, shows how the interpretation and manipulation of missed acts leads, ironically, to the Act. The influence of the psychodrama exerted there is found in other films, where the scene becomes the place where the abreaction becomes visible. Repetition of a formula in the obscure and forgotten sense (8 and ½), a crisis orchestrated by Sade as a playmaker (Marat-Sade), or a collective explosion (La vie est un roman) show the complex and multiple faces of the Act in cinema.